Couples' Retirement under Individual Pension Design: A Regression Discontinuity Study for France - Elena G. F. Stancanelli (Institute for the Study of Labor (IZA), 2016)
Retirement policies are individually designed but the majority of people of retirement age live as couples. We estimate the effects of a French pension reform on spouses' employment decisions. We use labor-force survey data, pooled over different years, on fifty thousand French couples and apply a regression discontinuity framework, also controlling for couple's unobserved heterogeneity. We conclude that the reform immediately reduced both spouses' retirement probability. The wife's retirement probability also drops by 1 to 4 percentage points if the husband is hit by the reform, and vice-versa. Instrumenting spousal retirement with legal retirement age, own retirement probability rises by 2 to 6 percentage points upon spousal retirement.
Keywords: J14; C1; C36; D04; 330; policy evaluation; retirement; ageing